Protective effects of chronic humanin treatment in mice with diabetic encephalopathy: A focus on oxidative stress, inflammation, and apoptosis - Bulut, Ferah; Adam, Muhammed; Ozgen, Aslisah; Hekim, Munevver Gizem; Ozcan, Sibel; Canpolat, Sinan; Ozcan, Mete (Elsevier, 2023)
Diabetes is known to cause cognitive impairments through various mechanisms, including oxidative stress, inflammation, and apoptosis. Humanin (HN) has been shown to have protective effects on cognitive impairments induced by factors such as A & beta;, muscarinic receptor antagonists, and aging in rodents. However, the mechanisms underlying the protective effects of HN in the prefrontal cortex and hippocampus in the context of diabetes are not well understood. In this study, we aimed to investigate the potential protective role of HN on oxidative stress, inflammation, and apoptosis in mice with diabetes. We divided the mice into four groups, including a control group (treated with saline), a humanin group (treated with 4 mg/kg of HN), a streptozotocin (STZ) group (diabetic control), and an STZ+Humanin group. The mice were administered HN daily for 15 days. Our results showed that in the prefrontal cortex and hippocampus of the diabetes group, oxidative stress parameters, pro-inflammatory cytokines, apoptosis and, blood glucose levels were increased, while antioxidant and anti-inflammatory cytokines were diminished compared to the control group. However, HN treatment was able to modulate these markers, including blood glucose and the markers of oxidative stress, inflammation, and apoptosis. In conclusion, our findings suggest that hyperglycemia, oxidative stress, inflammation, and apoptosis may contribute to the development of diabetes-induced cognitive impairments. By regulating these changes with HN treatment, we may be able to positively contribute to the treatment of cognitive impairments induced by diabetes.
Keywords: Humanin; Prefrontal cortex; Hippocampus; Diabetes; Oxidative stress; Inflammation